Associação entre o ângulo de fase e a composição corporal de mulheres obesas submetidas à gastroplastia redutora com derivação em y de Roux - Rocha, Larissa Scarparo (2018)
Introduction: Phase angle (PA), cellularity indicator, and cellular function have been used as a prognostic index in patient’s submitted to bariatric surgery (BS), with a low PA value associated with a lower body weight (BW) loss. Objective: To associate PA with BW, Body Mass Index (BMI), body fat (BF) and lean body mass (LBM) of women submitted to BS during the fast weight lost phase of BW. Methodology: Twenty adult women were submitted to Roux-en-Y Gastric Bypass at the Clinical Hospital (CH) of the Federal University of Espírito Santo (UFES). The study was approved by the Research Ethics Committee of CH - UFES. The participants were evaluated in the preoperative period or at the moment 0 (M0) (24.0 ± 20.5 days), at moment 1 (M1) after BS (72.0 ± 19.5 days) and at moment 2 (M2) after BS (189, 0 ± 12.2 days). Were evaluated; BW (kg), height (m), BMI (kg/m²), BF (kg e %), LBM (kg e %) e PA (°) in all three moments. MG, AF and AF data were based on the analysis of electrical bioimpedance. After the Shapiro-Wilk normality test were performed, ANOVA followed by the Bonferroni test, or Friedman test were performed as well. Correlations were obtained by the Spearman or Pearson tests. The SPSS version 21.0 program was used and the level of significance adopted was P <0.05. Results: PA was 7.0 ± 0.7 ° at M0, 5.9 ± 0.7 ° at M1 and 5.9 ± 0.7 ° at M2, being smaller at M1 in relation to M0 and M2 in relation to M0 (P <0.01). The BW was lower (P <0.05) after BS at both moments; 91.8 ± 13.7 kg (M1) and 79.9 ± 13.8 kg (M2) when compared to M0 (108.9 ± 13.9 kg) and lower at M2, when compared to M1. The results were observed in relation to (BMI); 43.0 ± 5.2 kg / m² (M0), 36.2 ± 5.1 kg / m² (M1) and 31.4 ± 5.2 kg / m² (M2), BF (kg) 52.6 ± 8.6 kg (M0), 41.1 ± 8.6 kg (M1) and 33.0 ± 8.8 kg (M2) and LBM (kg); 56.2 ± 5.8 kg (M0), 50.7 ± 5.6 kg (M1) and 46.8 ± 5.5 kg (M2). Considering all the differences found between M1 and M0 and M2 and M1, a positive correlation (r = 0.42; p <0.01) was observed between the reduction of the PA and the reduction of the BW. Similar results were found between PA and reduction of (BMI) (r = 0.40, p <0.05) between the reduction of PA and the reduction of BF (r = 0.39, p <0.05). No significant correlation was observed between the reduction of PA and the reduction of LBM (kg).Conclusion: Reduction of PA was associated with the weight loss, BMI, and BF, although it was not correlated with LBM.